Erectile dysfunction and methadone maintenance therapy - Fitri Fareez R,; Ahmad Nazrun Shuid,; Rashidi MPM,; Isa Naina Mohamed, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Erectile dysfunction is one of the most common side effects of methadone affecting more than half of methadone patient population. The problem is associated with prominent reduced quality of life. Erectile dysfunction may perpetuate greater problem if left untreated as patients may opt to use harmful self-treatment such as abusing methamphetamine. This illicit drug use to overcome the side-effects of methadone may lead to polysubstance use disorder that further compromise addiction therapy. To overcome this issue, both practitioners and patients play a major role in the management of erectile dysfunction. Patient awareness regarding erectile dysfunction and its impact as well as doctor’s active intervention to detect erectile dysfunction, are essential to improve the detection rate and management of erectile dysfunction. Frequent screening of erectile dysfunction and its risk factors will help with the identification of patients suffering from erectile dysfunction. Multiple treatments options such as bupropion, trazodone and many more are available to treat erectile dysfunction which will be further explored in this review.